APPLYING NUMERICAL MODEL TO ASSESS ROLE OF MANGROVE FOREST IN WAVE ATTENUATION IN HAI PHONG COASTAL AREA - Vinh, Vu Duy (Vietnam Journal of Marine Science and Technology, 2015)
The mangrove forest in the coastal zone has not only a significance to environment but also an important role in wave attenuation and coast protection. However, quantitative assessment of the role of mangrove forest in wave attenuation is just new in Vietnam. This paper presents the results of applying a numerical model based on Deltf3d model system to research the role of mangrove forest in wave attenuation in coastal zone of Hai Phong. The model was set up with different scenarios in case of mangrove and without mangrove forest by bottom friction formulas of Baptist (2005), Collins (1972) and De Vries-Roelvink (2004). The results show: maximum wave height behind mangrove forest in the normal condition is below 0.1 m (Bang La - Dai Hop) and below 0.3 m (Ngoc Hai - Tan Thanh). Wave reduction coefficients vary from 0.15 - 0.6. In the case of small typhoon, maximum wave height behind mangrove forest is about 0.5 - 0.8 m, corresponding to average wave reduction coefficient at about 0.4 (Bang La - Dai Hop) and 0.32 (Ngoc Hai - Tan Thanh). In the case of big typhoon, maximum wave height behind mangrove forest is about 0.8 - 1.1 m, corresponding to average wave reduction coefficient at 0.28.